Isolation, synthesis, conjugates and polymeric nanosystems of natural products to improve bioavailability and activity: siphonochilones, oxazolo[2,3-a]isoquinolines, maslinic acid and cannabidiol - Fuentes Rios, David (UMA Editorial, 2026)
Throughout this Doctoral Thesis, a comprehensive approach has been taken toward the design, development, and evaluation of new bioactive compounds derived from natural products, combining classical methodologies such as isolation and derivatization with advanced strategies in organic synthesis and applied nanotechnology. Initially, the chemical richness of Siphonochilus aethiopicus, a plant of ethnopharmacological interest, was explored through the isolation of natural compounds, such as siphonochilone and a new eudesmane-type sesquiterpenoid. Although their antitumor activity was limited, this work laid the foundation for the subsequent development of structurally optimized derivatives with greater potency and versatility. The derivatization of natural molecules, such as maslinic acid, led to the creation of new chemical entities, particularly the 48f conjugate (maslinic acid-tyramide), which showed a significant improvement in cytotoxic activity against various cancer types, including glioblastoma and drug-resistant colon cancer. This approach, based on targeted structural modification, proved to be the most effective strategy in terms of enhancing biological activity without compromising the original compound’s biocompatibility. In parallel, novel synthetic routes were developed for oxazolo[2,3-a]isoquinoline-type structures, and the first CBD-based polymeric drug was synthesized, establishing an innovative route for the incorporation of active compounds into stable, functional polymeric platforms. This phase of the thesis highlighted that rational synthesis, supported by an understanding of action mechanisms and physicochemical properties, is essential for designing compounds with real therapeutic applications. The final phase focused on the vehiculization of these compounds into smart polymeric nanosystems, including pNIPAM and p4VP nanoparticles, polymeric nanofibers, and functionalized magnetic hybrid systems. These systems significantly enhanced the solubility, stability, controlled release, and bioavailability of natural compounds, particularly CBD and the 48f derivative. Additionally, some systems (such as solid@p4VP-CBD) demonstrated the ability to protect the active compound under gastrointestinal conditions, supporting its potential for oral therapeutic use. Overall, this thesis demonstrates that integrating natural products into nanotechnological platforms is a multidisciplinary and effective strategy for generating new therapeutic tools. By merging nature’s chemical legacy with molecular design and nanotechnology, a promising pathway is opened for the development of more effective, selective, and adaptable drugs, tailored to the demands of modern medicine, particularly in the field of oncology.
Keywords: Cáncer; Cannabinoides; Drug discovery and delivery; Polymer nanosystem; Terpenes; Oxazolo[2,3-a]isoquinoline; Cannabidiol